Willpower as Cultural Construct: Do Chinese Students Believe Less in Its Depletion? - Sun, Xin; Cortina, Kai S.; Miller, Kevin F.; Ning, He (Frontiers in Psychology, 2019)
The idea of ego-depletion has been examined extensively in western cultures, but cultural background might substantially influence the understanding and effect of the concept. In the present study we used Job, Dweck, and Walton (2010)'s Implicit Theories on Willpower Questionnaire to examine whether Chinese college students, compared to US students, are less inclined to believe that willpower depletes. Applying two-group confirmatory structural equation modeling, the questionnaire with its two subscales – depletion of mental resources and depletion of resistance to temptation – showed consistent psychometrical qualities across both samples. As predicted, Chinese student believed less in the concept of depletion of mental resources than US students. However, Chinese students showed a stronger belief in the depletion of resisting temptation compared to their US counterparts, suggesting different normative contexts for the response to the two subscales across cultures.